The Effects of Student Overpopulation on the Academic Performance of the Intensive Advanced English I Students, Group 02 of the English Teaching Major at the Foreign Language Department of the University of El Salvador, Central Campus, Semester II-2018 - Calderón Aguillón, Oscar Antonio; Domínguez Tolosa, Angel Adonay; López López, Walter Humberto (2024)
The present work specifies the elements of the investigation to be carried out. The research topic is delimited in terms of scope, time and space. The objectives and purpose of the research are also defined. In addition, a synopsis of the project in general terms is also provided. The methodology used throughout the development of the investigation is also explained in detail. A chart with activities and dates of the research project is also presented.The investigation is developed based on an inductive approach, making use of a descriptive research. To achieve satisfactory results and reliable information, this project has obtained all data from the academic administration in the Schools of Arts and Sciences, administrative employees, professors and students of the Foreign Language Department.